(untitled) (Brazilian Journal of Radiation Sciences, 2021)
With technological advances in several research areas of science, it is becoming increasingly common to use computer programs to solve problems. Some of these programs are based on statistical analysis and simulation of reality, such as the Monte Carlo Method (MC). The MC is a statistical tool widely used in different areas of knowledge, as a resource for simulating events that involve from financial assessments to the interaction of radiation with matter. Thereby, surveys with radiation sources, for example, are constantly evolving to study the question of radiation protection. In this sense, this paper has as main objective to verify the relevance of the MC for the area of radiation protection, analyzing the studies that apply the method in the Postgraduate Program (PPG) in Radiation Protection and Dosimetry of Institute of Radiation Protection and Dosimetry (IRD). This is because it is understood thatthrough the application of Scientific Knowledge Management (SKM) the construction of knowledge happens through an exchange of scientific information, that is, exchange of relevant contents that help in the preservation of knowledge.In this sense, a bibliometric analysis of the dissertations and theses deposited in Brazilian bank was made using the search term "Monte Carlo" and its respective programs (PENELOPE, GEANT4, EGSnrc, MCNP and Visual Monte Carlo), to be found in the title, abstract or keywords. With the identification of works carried out in all areas of concentration of the PPG, it is understood that the MC is extremely relevant for studies in the area of radiation protection.